2015
DOI: 10.1080/14783363.2015.1087841
|View full text |Cite
|
Sign up to set email alerts
|

Public quality – for whom and how? Integrating public core values with quality management

Abstract: Quality management (QM) plays an important role in public organisations' efforts to create better access to, and effectiveness of, specific services. When transferring QM models from market-based firms to public services provided by public organisations, several basic contrasts and even contradictions must be addressed. Core values of the public sector differ from those of the private sector, but what are the consequences of this distinction? In this article we discuss the importance of four central arguments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
(29 reference statements)
0
15
0
2
Order By: Relevance
“…Lyons et al (2006) also found that public sector employees displayed lower levels of organizational commitment than private sector employees. In the context of Swedish private and public organizations, Elg et al (2015) stated four key arguments that distinguish private and public services: rights and access, equality, coerciveness, and legitimacy. The core values of public organizations are primarily influenced by legislation, publicity in the society, and politics, as opposed to profit-maximization in their private counterparts.…”
Section: Differences Between Private and Public Organizations In Busimentioning
confidence: 99%
“…Lyons et al (2006) also found that public sector employees displayed lower levels of organizational commitment than private sector employees. In the context of Swedish private and public organizations, Elg et al (2015) stated four key arguments that distinguish private and public services: rights and access, equality, coerciveness, and legitimacy. The core values of public organizations are primarily influenced by legislation, publicity in the society, and politics, as opposed to profit-maximization in their private counterparts.…”
Section: Differences Between Private and Public Organizations In Busimentioning
confidence: 99%
“…Complaints can be considered part of the concept of performance (Moynihan, 2008; Bouckaert and Halligan, 2007; Boyne et al , 2009; Ruffini et al , 2011; Behn, 2003; Rebora et al , 2016), mostly while talking about service quality (Suarez-Barraza et al , 2009; Nalbandian, 2013; Elg et al , 2015), or provision with a focus on topics such as red tape and corruption. This is made possible by evaluating and assessing services on the basis of expectations and perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some years ago, municipal organizations belonging to local public administration transformed their operation as a result of changes driven by new customer or user requirements through new developmental projects. Particularly in recent decades, public organizations have focused on bringing to their practices some concepts for improving the quality of what they deliver to society (Elg et al , 2017). Quality certification is one of those aspects.…”
Section: Introductionmentioning
confidence: 99%